2016
DOI: 10.1039/c6cc07022a
|View full text |Cite
|
Sign up to set email alerts
|

Combined covalent and noncovalent carboxylation of carbon nanotubes for sensitivity enhancement of clinical immunosensors

Abstract: We report here for the first time with quantitative details that the combination of pi–pi stacking of pyrenecarboxylic acid with chemically carboxylated multiwalled carbon nanotubes (MWNT-COOH) offers superior sensitivity compared to MWNT-COOH alone for serum insulin measurements and that this combination is broadly applicable for biosensors, drug delivery, and catalytic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The main challenge in the preparation of CNTs is to prevent the formation of CNT aggregation and achieve their optimal dispersion into a polymer matrix [105,106]. Many studies have shown that functionalization is the most effective way to modify the surface of CNT under strong acidic conditions, including covalent and non-covalent [107,108,109]. Covalent functionalization is the formation of new chemical bonds with the surface of nanotube sidewalls through some chemical reaction, such as oxidation, hydrogenation, halogenation, halogenation, etc.…”
Section: Concerns and Current Solutions Of Cnts As Nanomaterials Fmentioning
confidence: 99%
“…The main challenge in the preparation of CNTs is to prevent the formation of CNT aggregation and achieve their optimal dispersion into a polymer matrix [105,106]. Many studies have shown that functionalization is the most effective way to modify the surface of CNT under strong acidic conditions, including covalent and non-covalent [107,108,109]. Covalent functionalization is the formation of new chemical bonds with the surface of nanotube sidewalls through some chemical reaction, such as oxidation, hydrogenation, halogenation, halogenation, etc.…”
Section: Concerns and Current Solutions Of Cnts As Nanomaterials Fmentioning
confidence: 99%
“…Numerous studies have shown that functionalization is the most appropriate method to improve CNT exteriors in severely acidic environments [ 34 , 35 , 36 ]. Covalent functionalization was used to create novel hydrogen bonds on the nanoparticle surfaces to obtain a certain chemical response, such as hydrogenation, oxidative stress, or alkylation.…”
Section: Cnts In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…Such surface carboxylic acid enrichment on commercially purchased gold screen‐printed electrodes modified with MWNT−COOH/Py, used for insulin‐antibody immobilization, improved the sensitivity of peroxidase label‐based sandwich immunosensing of serum insulin. In that prior report, a quinone mediator was used for amperometric detection . In contrary, in the case of BOD enzyme, the surface‐enriched −COOH groups do not proportionately increase the covalently immobilized BOD‐electrocatalyzed direct O 2 reduction currents.…”
Section: Methodsmentioning
confidence: 99%